2004
DOI: 10.1038/sj.jp.7211058
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Economic Outcomes in Patients Treated for Recurrent Preterm Labor

Abstract: Treating RPTL with SQT versus oral nifedipine resulted in a later GA at delivery, improved neonatal outcome, and increased cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…When administered orally, terbutaline's efficacy is often greatly influenced by poor patient compliance and the development of myometrial desensitization related to long-term, high-dose exposure [3]. Continuous subcutaneous terbutaline therapy (SQT) has been reported to be more effective than oral tocolytics for pregnancy prolongation following acute preterm labor in both singleton and multiple gestations [4][5][6], and is safe from serious side effects when used appropriately [7].…”
Section: Introductionmentioning
confidence: 99%
“…When administered orally, terbutaline's efficacy is often greatly influenced by poor patient compliance and the development of myometrial desensitization related to long-term, high-dose exposure [3]. Continuous subcutaneous terbutaline therapy (SQT) has been reported to be more effective than oral tocolytics for pregnancy prolongation following acute preterm labor in both singleton and multiple gestations [4][5][6], and is safe from serious side effects when used appropriately [7].…”
Section: Introductionmentioning
confidence: 99%
“…recurrent preterm labor) were eligible for inclusion [11], [13]–[20]. Some studies were conducted exclusively in women with singleton gestation [13], [15], [17], [18], [21], [22], while a few studies evaluated women with twins only [16], [19]. Some studies may have included women less than 24 weeks gestational age, but data for such participants could not be separated [11], [15][19], .…”
Section: Resultsmentioning
confidence: 99%
“…Three retrospective cohort studies reported non-significant differences in rate of stillbirth in women with recurrent preterm labor and single or twin gestation [17][19]. However, these studies were likely underpowered, given the small number of events (<1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matched pairs (142) of women hospitalised with recurrent preterm labour were randomised to nifedipine or subcutaneous terbutaline [64]. Subcutaneous terbutaline resulted in a later gestation age at delivery, higher birth weights and less nursery days [65].…”
Section: Calcium-channel Blockersmentioning
confidence: 99%